Study on the Selection System of Arbitrators for Ad Hoc Arbitration in China - Zhengyan Zuo (Studies in Law and Justice, 2024)
The selection of arbitrators, as the beginning and core of ad hoc arbitration procedure, needs to be fully regulated by legislation, and the existing norms do not well meet the needs of the selection of arbitrators. Based on the theoretical foundation of autonomy, we explore the constituent elements of the system for the selection of arbitrators in ad hoc arbitration under the international perspective, sort out the existing system and deficiencies in our country, and make suggestions for the improvement of the system for the selection of arbitrators in ad hoc arbitration in our country: on the one hand, we should stipulate the loose conditions for the service of the arbitrators, improve the way of selecting arbitrators, and safeguard the party’s autonomy; on the other hand, we should take the intervention of the institution as the supplement to the party’s autonomy, and solve the deadlock of the selection. On the other hand, institutional intervention should be used as a supplement to party autonomy to resolve the deadlock in the selection. At the same time, the rules on the obligation to disqualify arbitrators should be improved to safeguard the independence of arbitrators and realize justice in arbitration.